Design and synthesis of novel hydroxamic acid derivatives based on quisinostat as promising antimalarial agents with improved safety - Manjiong Wang; Tongke Tang; Zhenghui Huang; Ruoxi Li; Dazheng Ling; Jin Zhu; Lubin Jiang; Jian Li; Xiaokang Li (Acta Materia Medica, 2022)
In our previous work, the clinical phase II HDAC inhibitor quisinostat was identified as a promising antimalarial agent through a drug repurposing strategy, but its safety was a matter of concern. Herein, further medicinal chemistry methods were used to identify new chemical entities with greater effectiveness and safety than quisinostat. In total, 38 novel hydroxamic acid derivatives were designed and synthesized, and their in vitro antimalarial activities were systematically investigated. These compounds at nanomolar concentrations showed inhibitory effects on wild-type and drug-resistant Plasmodium falciparum strains in the erythrocyte stage. Among them, compound 30, after oral administration, resulted in complete elimination of parasites in mice infected with Plasmodium yoelii, and also exhibited better safety and metabolic properties than observed in our previous work. Mechanistically, compound 30 upregulated plasmodium histone acetylation, according to western blotting, thus suggesting that it exerts antimalarial effects through inhibition of Plasmodium falciparum HDAC enzymes.